En defensa del territorio: las coaliciones militares antirromanas en el Pirineo occidental (siglos II–I a.C.) - Lanz, Jokin (Rzym a Półwysep Iberyjski: Inspiracje i powiązania na przestrzeni dziejów, 2021)
After the arrival of Rome in the western surroundings of the Pyrenees, some of the communities that inhabited the region quickly formed coalitions to defend their territory and were able to face the foreign power. For this purpose, strong mechanisms were used that were deeply rooted in the region and had proved to be capable of creating large military coalitions amongst different communities, giving them a certain military strength, and by adopting, when necessary, typically Roman military techniques. The attitude of some of these communities was clear evidence of the high degree of cohesion and ethnic consciousness that they had previously developed.